Treatment of synthetic refinery wastewater in anoxic–aerobic sequential moving bed reactors and sulphur recovery. Issue 13 (10th November 2017) - Mallick, Subrat Kumar; Chakraborty, Saswati
ABSTRACT: Objective of the present study was to simultaneously biodegrade synthetic petroleum refinery wastewater containing phenol (750 mg/L), sulphide (750 mg/L), hydrocarbon (as emulsified diesel of 300 mg/L), ammonia-nitrogen (350 mg/L) at pH >9 in anoxic–aerobic sequential moving bed reactors. The optimum mixing speed of anoxic reactor was observed at 20 rpm and beyond that, removal rate remained constant. In anoxic reactor the minimum hydraulic retention time was observed to be 2 days for complete removal of sulphide, 40–50% removal of phenol and total hydrocarbons and 52% of sulphur recovery. The optimum HRT of aerobic moving bed reactor was observed as 16 h (total HRT of 64 h for anoxic and aerobic reactors) for complete removals of phenol, total hydrocarbons, COD (chemical oxygen demand) and ammonia-nitrogen with nitrification.